Forest biodiversity and the delivery of ecosystem goods and services: translating science into policy - Thompson, I.D.; Okabe, K.; Tylianakis, Jason M.; Kumar, P.; Brockerhoff, E.G.; Schellhorn, Nancy A.; Parrotta, J.A.; Nasi, Robert (2011)
Biodiversity is integral to almost all ecosystem processes, with some species playing key functional roles that are essential for maintaining the value of ecosystems to humans. However, many ecosystem services remain nonvalued, and decisionmakers rarely consider biodiversity in policy development, in part because the relationships between biodiversity and the provision of ecosystem services are not generally appreciated. To date, the majority of work in which the functional importance of biodiversity has been examined has been conducted in relatively species-poor systems. Focusing on forest and agroforest systems, we synthesize recent research on the role of biodiversity in the provision of ecosystem services and provide examples of biodiversity science that informs ecosystem management and policy. Finally, we highlight barriers to the transfer of knowledge from scientists to decisionmakers and suggest that scientists can be much more effective at informing policy and improving resource management by asking policy-relevant questions and providing timely and consistent information to decisionmakers and the public on the linkages among biodiversity, ecosystem services, and their value to people.